Teachers' Questioning Strategies as a Scaffold to the Middle School Students’ Knowledge Building in Constructing Hortatory Exposition Texts: A Thematic Analysis - Gunawan, Wawan; Wirza, Yanty (International Journal of Language Education, 2025)
This study aims to analyze themes as elements of teachers’ questioning strategies as a scaffold for learners to understand and construct knowledge and their contribution to presenting knowledge in writing. This study followed a qualitative case research design involving two teachers who differed in their experience profiles in the teaching of hortatory exposition to 11th-grade EFL students in the Indonesian context. The data included teachers' questions and students' texts analyzed by deploying the conception of a Theme system in Systemic Functional Linguistics to identify how themes present a topic, contribute to the management of interaction, and structure ideas. The findings show that both teachers emphasized more on topical themes that function to familiarize the learners with the topics than themes that function to hedge and confirm the topics. These thematic features contribute to constructing emerging and distinctive features of the students’ hortatory exposition writing. It was found that the novice teacher posed more frequent questions on all themes that indicated more varied questioning strategies. Moreover, the quality of the students’ hortatory exposition essays relied on the presentation and sequence of themes and arguments attributed to the teachers’ questions. Overall, the study indicates the significance of teachers' questioning strategies for eliciting the students’ presentation and construction of knowledge in their argumentative style.